Traditional uses and emerging therapeutic potential of Typha angustifolia L.: insights into its phytochemistry, pharmacological activities and quality control - Liu, Junyu; Chen, Ziyi; Tao, Sian; Shu, Xinyao; Shao, Bingjie; Zhang, Xiaobo; Yang, Yang; Wang, Xiaoli (Frontiers in Pharmacology, 2025)
Typha angustifolia L. is a perennial marsh botanical drugs belonging to the genus Typha of the family Typhaceae, boasts a medicinal legacy spanning over 1900 years in China. Within traditional medicine, it is often used to treat a variety of bleeding disorders and gynecological diseases. Typha angustifolia contains various active components and metabolites including flavonoids, steroids, phenylpropanoids and organic acids. Over 94 compounds have been isolated and identified from T. angustifolia, demonstrating significant pharmacological activities such as anti-inflammatory, analgesic, anti-platelet aggregation, anti-atherosclerosis and anti-oxidation. In modern clinical practice, T. angustifolia is extensively utilized in treating dysmenorrhea, irregular menstruation, trauma bleeding, soft tissue contusion, hematochezia, hematuria and abnormal uterine bleeding. Typha angustifolia has a wide range of biological activities, making it a valuable resource for discovering potential drug candidates and developing new botanical supplements. This paper provides a comprehensive review of the research status of T. angustifolia, encompassing its botany, traditional uses, phytochemistry, pharmacological activity, and quality control, with the objective of enhancing our understanding of the application value and bioavailability of this traditional medicinal plant and offering a reference point for further research in this field.